DEVELOPMENT OF SETS-BASED CHEMISTRY TEACHING MATERIALS AND STUDENT RESPONSES TO TEACHING MATERIALS ON HYDROCARBON MATERIALS - Jessica Christine Rosalina Silaen; Saronom Silaban (Jurnal Scientia, 2022)
The purpose of this study was to determine the feasibility of SETS-based chemistry teaching materials on hydrocarbon materials based on BSNP criteria and to determine student responses to the developed teaching materials. This research method uses research and development (R&D) with the ADDIE development model. The ADDIE development model has five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The stages of this research are carried out until ADD (analysis, design, development) only. The results showed that the teaching materials that had been developed had met the eligibility criteria according to the BSNP standard based on the content feasibility aspect, the presentation feasibility aspect, and the language feasibility aspect, respectively, namely 89.44%, 88.43%, and with valid/feasible criteria. . While the results of student responses to the designed teaching materials are very high with an average percentage of 89.78%. It can be concludedSETS-based chemistry teaching materials on hydrocarbon materials developed have met BSNP standards and are suitable for use.